Voces. La voz de los mesenios bajo el dominio espartano - Plácido, Domingo (ARYS. Antigüedad: Religiones y Sociedades, 2020)
The aim of this paper is underline how during the spartan domination there are forms of expression what are strictly messenian and which would be the means used to make them known, in religion and in myths. So, it is possible to claim the validity of the sources on an interpretation that considers the character of their creation.